Актуальность определения ответственности за нарушение качества электроэнергии по показателям колебаний напряжения - Сендерович, Геннадий Аркадиевич; Дяченко, Александр Васильевич (НТУ "ХПИ", 2016)
В статье рассмотрены физические процессы при колебаниях напряжения, способы измерения и расчетов показателей их характеризующих, влияние колебаний напряжения на электрооборудование и мероприятия по его снижению. Сделан вывод о целесообразности проведения исследований по определению ответственности субъектов в случае превышения колебаниями напряжения допустимых значений.

As showed by results of research: fluctuations of voltage make negative impact on sight of the person and functioning of the electric equipment; in a network there is a large number of possible sources of fluctuation of tension; there are ways of identification of fluctuation of voltage; there are methods of decrease in fluctuation of voltage. The analysis of literature didn't reveal development by definition of responsibility of subjects for violation of requirements to quality of electric energy regarding fluctuations of voltage.
The relevance of determining responsibility for violation of power quality in terms of voltage fluctuations
Keywords: показатели качества электроэнергии; электромагнитная совместимость; фликер; размах изменения напряжения; electromagnetic compatibility; fluctuations of tension; fliker